The Steps to Therapeutic Drug Monitoring: A Structured Approach Illustrated With Imatinib - Buclin, Thierry; Thoma, Yann; Widmer, Nicolas; André, Pascal; Guidi, Monia; Csajka, Chantal; Decosterd, Laurent A. (Frontiers in Pharmacology, 2020)
Pharmacometric methods have hugely benefited from progress in analytical and computer sciences during the past decades, and play nowadays a central role in the clinical development of new medicinal drugs. It is time that these methods translate into patient care through therapeutic drug monitoring (TDM), due to become a mainstay of precision medicine no less than genomic approaches to control variability in drug response and improve the efficacy and safety of treatments. In this review, we make the case for structuring TDM development along five generic questions: 1) Is the concerned drug a candidate to TDM? 2) What is the normal range for the drug’s concentration? 3) What is the therapeutic target for the drug’s concentration? 4) How to adjust the dosage of the drug to drive concentrations close to target? 5) Does evidence support the usefulness of TDM for this drug? We exemplify this approach through an overview of our development of the TDM of imatinib, the very first targeted anticancer agent. We trust that a similar story shall apply to other drugs in this class, as well as to a wide range of critical treatments for controlling various life-threatening conditions. Despite hurdles that still jeopardize progress in TDM, there is no doubt that upcoming technological advances will shape and foster many innovative therapeutic monitoring methods.